Audels plumbers and pipe fitters library : drainage, fittings, fixtures - Oravetz, Jules A. (Indianapolis : T. Audel, 1967)
Plumbing and pipe fitting play major roles in the construction of all types of residential, commercial, and industrial buildings. Of all the building trades, the plumbing trade is most essential to the health and well-being of the community in general, and to the occupants of the buildings in particular.
Includes index.
II 15/01/2019
Loans
Keywords: Plumbing; Pipe fitting